Defensive Mechanisms and Managerial Discretion - Giammarino, Ronald; Heinkel, Robert; Hollifield, Burton (Journal of Finance, 1997)
We study a model where firms may possess free cash flow and takeovers may be disruptive. We show that the possibility of a takeover, combined with defensive mechanisms and the ability to pay greenmail, can solve the free cash flow problem in an efficient way. The payment of greenmail reveals information that generates a stock price decline that exceeds the value of the greenmail payment, even though the payment of greenmail is value maximizing. Optimal defensive measures limit takeover attempts if the target stock price is too low. We also provide cross-sectional implications of the analysis.